Genomic analysis reveals the genetic diversity, population structure, evolutionary history and relationships of Chinese pepper - Feng, Shijing (Hortic Res, 2020)
Chinese pepper, mainly including Zanthoxylum bungeanum and Zanthoxylum armatum, is an economically important crop popular in Asian countries due to its unique taste characteristics and potential medical uses. Numerous cultivars of Chinese pepper have been developed in China through long-term domestication. To better understand the population structure, demographic history, and speciation of Chinese pepper, we performed a comprehensive analysis at a genome-wide level by analyzing 38,395 genomic SNPs that were identified in 112 cultivated and wild accessions using a high-throughput genome-wide genotyping-by-sequencing (GBS) approach. Our analysis provides genetic evidence of multiple splitting events occurring between and within species, resulting in at least four clades in Z. bungeanum and two clades in Z. armatum. Despite no evidence of recent admixture between species, we detected substantial gene flow within species. Estimates of demographic dynamics and species distribution modeling suggest that climatic oscillations during the Pleistocene (including the Penultimate Glaciation and the Last Glacial Maximum) and recent domestication events together shaped the demography and evolution of Chinese pepper. Our analyses also suggest that southeastern Gansu province is the most likely origin of Z. bungeanum in China. These findings provide comprehensive insights into genetic diversity, population structure, demography, and adaptation in Zanthoxylum.